(untitled) (Journal of the College of Basic Education, 2023)
This religious and doctrinal research clarifies the place of Heaven and Hell in the mortal abode, and what it includes from the sayings of scholars proves the place of Heaven and Hell in this world. I have arranged the research on the introduction, the study section, and the investigation section. The first chapter includes: introducing the author’s life, and the second chapter is a study of the book. As for the second section (the verified text) of the manuscript (The Mirror of the Hereafter), the chapter (in the place of Paradise and Hell from the mortal abode), and the purpose of my research is for the Muslim to know the place of Paradise and Hell from these The world.